Spectroflurimetric study of estrogen-cyclodextrin inclusion complexes in aqueous systems - Pérez, Rocío Laura (2013)
For the first time, the spectrofluorimetric properties of estrone (E1), 17β-estradiol (E2), estriol (E3), and 17α-ethinylestradiol (EE2) are studied in aqueous solutions after the addition of native and derivative cyclodextrins. In contrast to previous reports, the behavior of the systems is analysed in the absence of organic solvents able to modify the guest-host interaction. The significant differences between the obtained association constants with those reported in solvent mixtures are shown and discussed. In order to evaluate the influence of both the estrogen structure and the presence of cyclodextrin substituents in the inclusion phenomena, fluorescent and acid-base behaviors of the systems are compared and discussed. The interaction of estrogens with micellar media formed by selected surfactants is also studied. It is demonstrated that estrogen-cyclodextrin complexes in aqueous solution are useful for improving fluorimetric detection limits and, since cyclodextrins are non-toxic and mitigate most of the solubility problems which require the use of organic solvents, the studied complexes are excellent candidates for extraction, separation, pre-concentration and removal processes maintaining the principles of the green analytical chemistry.